Impact of an acute surgical unit in appendicectomy outcomes: A systematic review and meta-analysis. (February 2018) - Balasubramanian, Ishwarya; Creavin, Ben; Winter, Des
Abstract: Background: The provision of emergency general surgical services is undergoing a paradigm shift towards a consultant led, patient centered model in order to improve patient outcomes. The aim of this current study is to use meta-analytical techniques to assess the efficacy of acute surgical unit (ASU) in appendectomy. Methods: A meta-analysis was conducted according to the PRISMA guidelines. A comprehensive literature search of PubMed, Embase and Scopus for published studies comparing ASU and traditional (TRAD) model on appendectomy outcomes was performed. Random-effects methods were used to analyze key outcomes with data presented as odds ratio (OR) with 95% confidence interval (CI). Results: Fourteen comparative studies describing outcomes in 7980 patients were identified, 4258 patients were included in the ASU model (53.4%). ASU model had a shorter time to theatre (WMD: −0.40, 95% CI: −0.65 to 0.15, p: 0.002), length of hospital stay (WMD: −0.25, 95% CI: −0.46 to −0.05, p: 0.02) and complication rate (OR: 0.76, 95% CI: 0.59 to 0.99, p: 0.04) for appendectomy patients. ASU model did not significantly affect night time operating (OR: 1.04, 95% CI: 0.66 to 1.65, p: 0.86) negative appendectomy rates (OR: 0.98, 95% CI: 0.77–1.27, p: 0.91) or conversion rate (OR: 1.45, 95% CI: 0.70 to 2.98, p: 0.32). Conclusion: ASU model improves outcomes and quality of care in patients undergoing emergency appendectomy without any adverse implications. Highlights: This is the largest analysis demonstrating the positive effect of ASU model on key performance indicators in acute appendicitis. Early senior decision making and time to theatre are key aspects of the ASU model that are associated with improved outcomes. This study highlights that there is no one size fits all universal ASU model to suit all hospitals. ASU models can be tailored to meet the needs of both tertiary and smaller community hospitals.